2014
DOI: 10.1021/jp509183k
|View full text |Cite
|
Sign up to set email alerts
|

Zn2SnO4-Based Photoelectrodes for Organolead Halide Perovskite Solar Cells

Abstract: We report a new ternary Zn 2 SnO 4 (ZSO) electron-transporting electrode of a CH 3 NH 3 PbI 3 perovskite solar cell as an alternative to the conventional TiO 2 electrode. The ZSO-based perovskite solar cells have been prepared following a conventional procedure known as a sequential (or two-step) process with ZSO compact/mesoscopic layers instead of the conventional TiO 2 counterparts, and their solar cell properties have been investigated as a function of the thickness of either the ZSO compact layer or the Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(40 citation statements)
references
References 29 publications
1
39
0
Order By: Relevance
“…This is because, besides the faster electron transport BaSnO3 and SrTiO3 have a better contact with perovskite, which makes the crystals grow more unity and the scaffold have a better surface coverage, resulting in a high shunt resistance and improved performance compared with the conventional mesoporous TiO2 in the control device. Recently, Bera et al [26] also reported that the mesoporous ternary oxide Zn2SnO4 could significantly promote the crystallization of hybrid perovskite layers and serve as an efficient electron transporting material in perovskite solar cells, although the Zn2SnO4 was firstly used as ETL in MPSC by Oh et al [27]. Both of them noticed that the Zn2SnO4-based PSC exhibited much faster electron transport and superior charge collection capability than TiO2-based PSC under similar condition.…”
Section: Methodsmentioning
confidence: 99%
“…This is because, besides the faster electron transport BaSnO3 and SrTiO3 have a better contact with perovskite, which makes the crystals grow more unity and the scaffold have a better surface coverage, resulting in a high shunt resistance and improved performance compared with the conventional mesoporous TiO2 in the control device. Recently, Bera et al [26] also reported that the mesoporous ternary oxide Zn2SnO4 could significantly promote the crystallization of hybrid perovskite layers and serve as an efficient electron transporting material in perovskite solar cells, although the Zn2SnO4 was firstly used as ETL in MPSC by Oh et al [27]. Both of them noticed that the Zn2SnO4-based PSC exhibited much faster electron transport and superior charge collection capability than TiO2-based PSC under similar condition.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the ETL can provide a larger interface contact site to load the perovskite pigments and afford faster charge extraction . To date, many ETL materials such as ZnO, Nb 2 O 5 , SnO 2 , CdS, ZnSnO 3 , SrTiO 3 , and WO 3 have been successfully applied to PSC devices. Among them, mesoporous TiO 2 is the most widely used.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] Thet ypical PSC device consists of an anode,e lectrontransport layer (ETL), perovskite absorption layer, holetransport layer (HTL), and cathode.T he ETL is used to collect and transport electronsi nt he process of converting solar energy into electricity.I naddition, the ETL can providea larger interface contacts ite to load the perovskite pigments and afford faster charge extraction. [15] To date,m any ETL materials such as ZnO, [16,17] Nb 2 O 5 , [18,19] SnO 2 , [20,21] CdS, [22,23] ZnSnO 3 , [24][25][26] SrTiO 3 , [27,28] and WO 3 [29] have been successfully applied to PSC devices.A mong them, mesoporousT iO 2 is the most widely used. However, ag reat deal of interfacetrap states are formed in the mesoporous TiO 2 layer during the processo ff abricating PSC devices, [30][31][32][33] and trap states have an egative effecto nc harge recombination and charget rans-port, which in turn influences the solar cell voltage and current.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many studies to match appropriate hole-transport materials (HTMs) with LAMs in mesoscopic devices. [14,15] Those approaches were effective for adjusting electron transport and recombination properties and device stability. [7,8] Ah igh performance and less hysteresis in photovoltaicp roperties could be obtained by modifying the meso-porousE TM.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Recently,m etal-oxide-based mesoporous ETMs have been studied with emphasis on modifications of morphology/structure, [9] chemical/physical properties of the ETM/ LAM interfaces, [10] the electronic band structure, [11][12][13] and the materiali tself. [14,15] Those approaches were effective for adjusting electron transport and recombination properties and device stability.…”
Section: Introductionmentioning
confidence: 99%